SYNTHESIS OF KINA ALKALOID DERIVATIVES AND THEIR ANTIBACTERIAL ACTIVITY - TANYELA BERGHUIS NIM:30512023, NILA
The Cinchona plant (Cinchona sp.) is a medicinal plant that has been known for hundreds of years as an antimalarial, food additive and catalyst. One of the active compounds that have been isolated from the Cinchona plant is the alkaloid group. The structural diversity possessed by alkaloids can make it a new source of scaffold in drug synthesis, one of which is quinoline based alkaloids. Quinolines and their derivatives contained in many natural compounds have interesting physiological and biological properties. The quinine alkaloids play an important role in their utilization as chiral auxiliaries and their ability in transformation of functional groups and skeleton providers utilized in chemical or pharmacological reactions based on alkaloids structures. The quinine derived synthesis compound is found to have a wide spectrum of antibacterial activity, which gives a new starting point in the development of a class of antibacterial and antimicrobacterial agents. Active compounds used as antitherapeutic compounds, such as antibacterials, tend to have larger structural scaffolds and are more complex than compounds for other biological activities. Recognizing this need, a strategy for generating rapidly the collection of complex molecules has emerged. One approach is diversity-oriented synthesis through diversification of the scaffold, in which simple starting materials are added to create a variety of structures that are more like natural products in size, taking into account the number of C-sp3 as well as the number of stereogenic centers. This research is aimed to synthesis of Kina alkaloid derivatives and to evaluate their antibacterial properties. Twelve Kina alkaloid derivatives have been successfully synthesized based on quinine derivative compounds (35, 39, 40, 41, 42, 43, and 45), obtained from Wacker oxidation reactions, Oppenauer oxidation, oxime formation, and Beckmann fragmentation, two quinidine derivative compounds (44 and 46) obtained from Wacker and Oppenauer oxidation reactions, two cinchonine derivative compounds (47 and 48) obtained from Wacker oxidation reactions and Oppenauer oxidation reaction and one cinchonidine derivative compounds (49) from Oppenauer oxidation reaction. The identification of the synthesis compound was performed using a nuclear magnetic resonance (NMR) spectrometer, low resolution mass spectrometer (LR-ESIMS) and high resolution mass spectrometer (HR-ESIMS) and melting point measurements. The molecular structure of the compounds is determined based on the results of spectroscopic data analysis, which includes one dimensional (1D) and two dimensional (2D) nuclear magnetic resonance spectrum (NMR), mass spectra (MS) and functional group analysis using FTIR. Antibacterial testing was carried out againts four clinical isolates of patogenic bacteria, including Salmonella enterica, Salmonella dysentriae, Enterococcus faecalis and Staphylococcus aureus, using a microdilution method. The twelve derivatives were quinine-9-one (35), quinine N-oxide (39), quinine-di-N-oxide (40), quinine-9-on N-oxide (41), (Z)-8-ethyllidene-2- (6-methoxyquinoline-4-carbonyl) quiniclidine 1-oxide (42), quinine- 9-oxime (43), quinidine-9-oxime (44), 6- methoxyquinoline-4 carbonitrile (45), quinidine-9-one (46), cinchonin-9-one (47) , quinoline-4-yl (3- (3-vinylpiperidine-4-yl) oxirane-2-yl) methanon (48), and cinchonidine-9- one (49). Compounds 39, 42, and 48 are new chemical compounds. Antibacterial evaluation showed that the mixture of epimer of compounds 35 and 46; 43 and 44 and compound 39 exhibit weak activities but selective activity against one of the Gram- negative bacteria Salmonella enterica with the same MIC and MBC values (62,5 ?g/mL and >250(rumus)g/mL). The activities antibacterial of the compounds (35 and 46; 43 and 44 and 39) is similar to the activity of the amoxicillin as a antibiotic compounds against the same bacteria.